PENGELOLAAN DAN PERIZINAN PARIWISATA GUNUNG GEULIS LEARNING CENTER DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI SARANA KESEJAHTERAAN MASYARAKAT - Kusuma, Ibnu; Samhudi, Gamalel Rifqi (Collegium Studiosum Journal, 2024)
Tourism plays an important role in improving the economy and welfare of the community, especially through the development of tourist destinations in Indonesia that are rich in culture, history, and natural beauty. This research analyzes tourism management and licensing at the Gunung Geulis Learning Center in Jipang Village, Brebes Regency, as an effort to improve the welfare of the local community. The main focus of this research is on the potential for tourism development and management in Good Corporate Governance so that it can be applied accordingly so that inhibiting factors can be overcome such as management and facilities that must be fulfilled and the welfare of the surrounding community through community participation and government support. This researcher uses a normative juridical approach method intended as an effort to observe the problem being investigated with legal characteristics, books, laws and regulations, and other related documents. The results of this study can be input for the government and tourism managers in order to apply the principles of Good Corporate Governance.